Demographic and geographical variability in physiotherapy provision following hip and knee replacement. An analysis from the National Joint Registry for England, Wales, Northern Ireland and the Isle of Man. (March 2020) - Smith, Toby O.; Dainty, Jack R.; Clark, Emma M.; Whitehouse, Michael R.; Price, Andrew J.; MacGregor, Alex J.
Abstract: Background: Total hip (THR) and knee replacement (TKR) are two of the most common elective orthopaedic procedures worldwide. Physiotherapy is core to the recovery of people following joint replacement. However, there remains uncertainty as to physiotherapy provision at a national level. Objectives: To examine the relationship between patient impairment and geographical variation on the provision of physiotherapy among patients who undergo primary total hip or knee replacement (THR/TKR). Design: Population-based observational cohort study. Methods: Patients undergoing THR ( n  = 17, 338) or TKR ( n  = 20, 260) recorded in the National Joint Registry for England (NJR) between 2009 and 2010 and completed Patient Reported Outcome Measures (PROMs) questionnaires at Baseline and 12 months postoperatively. Data were analysed on the frequency of physiotherapy over the first postoperative year across England's Strategic Health Authorities (SHAs). Logistic regression analyses examined the relationship between a range of patient and geographical characteristics and physiotherapy provision. Results: Following THR, patients were less likely to receive physiotherapy than following TKR patients ('some' treatment by a physiotherapist within 1st post operative year: 53% vs 79%). People with worse functional outcomes 12 months postoperatively, received more physiotherapy after THR and TKR. There was substantial variation in provision of physiotherapy according to age (younger people received more physiotherapy), gender (females received more physiotherapy) ethnicity (non-whites received more physiotherapy) and geographical location (40% of patients from South West received some physiotherapy compared to 40 73% in London after THR). Conclusions: There is substantial variation in the provision of physiotherapy nationally. This variation is not explained by differences in the patient's clinical presentation.